Relasi Sosial dalam Pembelajaran di Maluku: Komunikasi Interpersonal dan Penguatan Kreativitas di Sekolah Berbasis Lingkungan - Tharob, Kristina; Lopulalan, Dortje Leonora Yokbeth (Populis: Jurnal Ilmu Sosial dan Ilmu Politik, 2022)
This study examines the effectiveness of interpersonal communication between educators and students in fostering creativity through an environment-based learning approach at Green Moluccas Nature School in Maluku. The focus lies in how social relations formed through interpersonal interaction can create a collaborative, open, and supportive learning space that enhances students' creative expression. Using a qualitative descriptive approach, data were collected through observation, in-depth interviews, and documentation. The data were analyzed using Miles and Huberman’s interactive model, comprising data reduction, display, and conclusion drawing. The findings reveal that students’ creativity is significantly influenced by the quality of interpersonal communication, particularly in terms of openness, empathy, equality, positive attitude, and active support from educators. Dialogic transactional communication fosters deep emotional understanding, enabling teachers to guide students contextually in environmental practices such as waste processing. The novelty of this study lies in its emphasis on integrating interpersonal communication into ecological pedagogy as a strategy to enhance creativity in island-based regions. This research contributes to the field of social sciences—especially the sociology of communication—by highlighting how interpersonal interaction functions not only as a medium of instruction but also as a transformative tool in socially and ecologically contextualized education.